The Impact of Training Methods And Flexibility on Smash Ability in Sepak Takraw - Heriansyah Heriansyah; Abdul Salman; Teguh Hartanto; Ruslan Abdul Gani (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to find out the differences in the influence of training models and flexibility on smash in sepak takraw. This research was conducted at the University Halu Oleo Kendari club. An experimental method with a simple 2X2 factorial design was used in this study. 40 samples were obtained through simple random sampling. The results showed that: 1) the plyometric training method had a better effect on smash ability in a sepak takraw compared with the weight training method, 2) In The high flexibility group, the plyometric training method got better effects than the weight training method, 3 ) In The low flexibility group, the weight training method has a better effect than the plyometric training method on smash ability in sepak takraw., 4) There was an interaction between the training method and flexibility of the Smash in the sepak takraw.